(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article deals with the art of the world’s classic drama on the stage of the Kazakh theatrein the last few years. Analyzed the performances of «Trojan Women» by Euripides musical drama theater of Turkestan, «Desire Under the Elms» Y.O’Nil in Zhetysay Drama Theatrenamed after K. Zhandarbekov, «Between Heaven and Earth» M. Levi in Astana Youth Theatre and «Othello» by Shakespeare in Zhambyl regional Kazakh Drama Theatre. Key words: theater, classical, playwright, director and actor.